2017
DOI: 10.1136/bmjopen-2017-017672
|View full text |Cite
|
Sign up to set email alerts
|

Development of a discussion tool to enable well-being by providing choices for people with dementia: a qualitative study incorporating codesign and participatory action research

Abstract: ObjectiveTo codesign a discussion tool to facilitate negotiation of risk between health professionals, people with dementia and carers.MethodsA qualitative approach using codesign. Thematic analysis was used to analyse interviews and focus groups with people with dementia, carers, healthcare staff and healthy older people exploring the issue of risk in dementia, the acceptability and development of a discussion tool.ResultsSixty-one participants identified the breadth, depth and complexity of risk in dementia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 16 publications
(11 reference statements)
1
16
0
Order By: Relevance
“…Research has shown that the active participation of all stakeholders throughout the design of technical systems and services helps ensure that the end product meets the needs of its intended user base, improves usability, and increases engagement of all individuals [27][28][29]. Importantly, there is an emerging evidence base reflecting the benefits of co-design with older adults, including those with dementia, and their family and caregivers, to enable strengths-based, person-centered care [30,31]. Our research team's established co-design methodologies explicitly position users as empowered participants in all stages from design and development through to implementation and impact evaluation [28,29,32,33].…”
Section: Participatory Designmentioning
confidence: 99%
“…Research has shown that the active participation of all stakeholders throughout the design of technical systems and services helps ensure that the end product meets the needs of its intended user base, improves usability, and increases engagement of all individuals [27][28][29]. Importantly, there is an emerging evidence base reflecting the benefits of co-design with older adults, including those with dementia, and their family and caregivers, to enable strengths-based, person-centered care [30,31]. Our research team's established co-design methodologies explicitly position users as empowered participants in all stages from design and development through to implementation and impact evaluation [28,29,32,33].…”
Section: Participatory Designmentioning
confidence: 99%
“…This paper describes the process of developing a mobile-enabled mHealth application for family caregivers of people with dementia to address needs related to functional disability care. Consistent with the previous health intervention studies 46,49,50,60 , a co-design process guided the development of the application. To our knowledge, this is the first reported mHealth application development study based on the co-design process that addresses the functional disability care needs of family caregivers of people with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…46 In recent history, this method has been widely used to develop health interventions. 46,49,50 This paper reports on the co-design, specifically the development process, of an mHealth application for family caregivers of people with dementia to address functional disability care needs.…”
Section: Co-design Processmentioning
confidence: 99%
“…In the context of community care, negotiating risk in activities of daily living can follow this approach depending on the level of cognitive impairment, needs, and preferences ( Dickins et al, 2018 ). In line with this, a risk negotiation discussion tool was codesigned with people with dementia, informal carers, and community aged care staff, with 12 areas of activities of daily living with potential risks consolidated from 59 original items ( Goeman et al, 2017 ). This “ Enabling Choices ” tool was developed and deemed acceptable for identifying and addressing concerns, supportive of the dignity and autonomy of the person with dementia ( Goeman et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, a risk negotiation discussion tool was codesigned with people with dementia, informal carers, and community aged care staff, with 12 areas of activities of daily living with potential risks consolidated from 59 original items ( Goeman et al, 2017 ). This “ Enabling Choices ” tool was developed and deemed acceptable for identifying and addressing concerns, supportive of the dignity and autonomy of the person with dementia ( Goeman et al., 2017 ). To ensure uptake of such a tool into practice, implementation science principles are of value to embed it within the community aged care context.…”
Section: Introductionmentioning
confidence: 99%